Impact of Abiotic Factors on Occurrence of Capsule Borer and Sucking Pests in Sesamum - Divya, P.; Dhurua, S.; Chalam, M. S. V.; Rao, S. Govinda; Chaitanya, Gummadidala (International Journal of Economic Plants, 2024)
A field experiment was conducted at Agricultural college, Naira, Srikakulam, Andhra Pradesh, India during early summer (January–April) of 2021 to know about the incidence of leaf webber and sucking pests viz., leafhopper (Hishimonus phycitis Distant) and whitefly (Bemisia tabaci Gennadius) its relation with main weather factors. Results revealed that a peak incidence of mean capsule borer population per plant were recorded in 9th and 11th standard weeks, respectively. The correlation study revealed that the Antigastra larvae had significantly positive correlation with maximum temperature (r=0.48) and significantly negative correlation with relative humidity (r=- 0.71). The regression analysis revealed that these factors accounted for approximately 59.8% of the variation in the capsule borer population (R2=0.598). The incidence of leafhopper (Hishimonus phycitis Distant) and whitefly (Bemisia tabaci Gennadius) were started during 5th and 4th SMW attained their peaks during 11th an 12th SMW respectively. The correlation study revealed that the leafhopper showed significant positive correlation with maximum temperature (r=0.623) and minimum temperature (r=0.283) and significantly negatively correlated with morning and evening relative humidity (r=-0.165, r=-0.122) respectively. While the correlation study between whitefly population and weather parameters revealed that the it showed positive correlation with maximum (r=0.821) and minimum (r=0.120) temperature and negatively correlated with morning and evening relative humidity (r=-0.097, r=-0.182) respectively whereas, rainfall showed non-significant correlation (r=0.00) with the both sucking pests.